2020
DOI: 10.1002/hlca.202000129
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)‐Rotundone and (−)‐epi‐Rotundone from Monoterpene Precursors

Abstract: The first total synthesis of (À)-rotundone has been accomplished from (+)-(R)-limonene and therefore for the first time from an unrelated monoterpene instead of modifying structurally closely related sesquiterpene precursors such as α-guaiene. Challenges such as intermediates with stereocenters prone to epimerization by enolization were overcome by designing a β-methyl-keto route starting from (+)-(R)-limonene which finally gave (À)-rotundone by Nazarov cyclization of a precursor 13a. Diastereomer (À)-epi-rotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A selection of the reported examples is shown in Figure 2. Singh et al reported the rearrangement of α-guaiene to 10-epi-zonarene (9) in concentrated sulfuric acid, [16] and the formation of corymbolone (10) was brought about by the oxidation of αguaiene. This transformation though was not a rearrangement in the classical sense but an oxidative cleavage of the endocyclic double bond followed by aldol reaction.…”
Section: Slight Structural Changes Examples Are Shown Inmentioning
confidence: 99%
See 4 more Smart Citations
“…A selection of the reported examples is shown in Figure 2. Singh et al reported the rearrangement of α-guaiene to 10-epi-zonarene (9) in concentrated sulfuric acid, [16] and the formation of corymbolone (10) was brought about by the oxidation of αguaiene. This transformation though was not a rearrangement in the classical sense but an oxidative cleavage of the endocyclic double bond followed by aldol reaction.…”
Section: Slight Structural Changes Examples Are Shown Inmentioning
confidence: 99%
“…13 C-NMR (150 MHz, C 6 D 6 ): 74.1 (s), 57.2 (d), 45.7 (s), 38.0 (t), 37.8 (d), 37.4 (t), 35.2 (t), 33.9 (t), 32.2 (q), 30.7 (s), 29.9 (t), 29.0 (d), 26.6 (t), 19.9 (q), 14.3 (q) ppm. GC/MS (EI): m/z (%): 220 (7) [M + ], 205 (4), 163 (100), 154 (10), 121(39), 105 (9), 91 (10), 79 (10), 41 (13) (1R,3aS,4S,7S,9aS)-9a-Hydroxy-1,4,7-trimethyloctahydro-3a,7-methanocyclopenta [8]annulen-9(4H)-one (22) To a suspension of pyridinium chlorochromate (2.13 g, 9.89 mmol) and celite (2.13g) in CH 2 Cl 2 (38 mL), a solution of (1R,3aS,4S,7S)-1,4,7-trimethyldecahydro-3a,7-methanocyclopenta [8]annulen-9-ol (20, 2.00g, 8.99 mmol) in CH 2 Cl 2 (30 mL) was added over 30 min. The mixture was stirred at room temperature for 25h, filtered over a layer of celite and silica and washed with 50 mL CH 2 Cl 2 .…”
Section: (1ar3s6s6as9r9as)-369-trimethyloctahydro-7h-36a-methanocyclo...mentioning
confidence: 99%
See 3 more Smart Citations